Just Culture, a misunderstood ”success”? - Bjørn,Kim; Grønlykke,Anders (2025)
Abstract: This bachelor thesis explores the concept of just culture within aviation, with a specific focus on European airline captains’ knowledge, understanding, and perception of their reporting obligations. Grounded in the theoretical just culture framework of safety culture, developed by James Reason (1997), the study examines whether the principles of just culture - now nearly 30 years old, and legally implemented through Regulation 376/2014 - function as originally intended, or whether the concept remains a work in progress. To investigate this, a qualitative research design was employed, using semi-structured interviews with 13 captains from European commercial airlines. The interviews aimed to assess the pilots’ familiarity with both mandatory and voluntary occurrence reporting, and how these practices relate to the broader goals of just culture in organizational safety management. The study finds that while pilots generally express a positive attitude toward just culture, its full potential - particularly in relation to reporting - has yet to be realized. The authors conclude that aviation organizations should actively enhance pilots’ conceptual understanding of just culture in order to strengthen its practical application and improve the frequency of occurrence reports.
Keywords: Just culture; Regulation 376/2014; reporting obligations; FLYL01